2014
DOI: 10.1136/bmj.g2267
|View full text |Cite
|
Sign up to set email alerts
|

The impact of antibiotics on growth in children in low and middle income countries: systematic review and meta-analysis of randomised controlled trials

Abstract: Objectives To determine whether antibiotic treatment leads to improvements in growth in prepubertal children in low and middle income countries, to determine the magnitude of improvements in growth, and to identify moderators of this treatment effect.Design Systematic review and meta-analysis.Data sources Medline, Embase, Scopus, the Cochrane central register of controlled trials, and Web of Science.Study selection Randomised controlled trials conducted in low or middle income countries in which an orally admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
96
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 78 publications
5
96
3
Order By: Relevance
“…Severely malnourished infants have been shown to gain weight faster when they are given antibiotics, [12][13][14][15] and similar findings have been only recently reported in well-nourished children in affluent Western countries. [7][8][9][10][11] Antibiotics increase body fat mass in mice, which is assumed to result from changes in composition of the intestinal microbial flora.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Severely malnourished infants have been shown to gain weight faster when they are given antibiotics, [12][13][14][15] and similar findings have been only recently reported in well-nourished children in affluent Western countries. [7][8][9][10][11] Antibiotics increase body fat mass in mice, which is assumed to result from changes in composition of the intestinal microbial flora.…”
Section: Discussionsupporting
confidence: 59%
“…In children with severe malnutrition or chronic infections such as HIV, several studies have shown that both weight gain and linear growth in height improved with antibiotic therapy. [12][13][14][15] However, the effect of early antibiotic exposure on height in healthy, well-nourished children has not been adequately elucidated. [7][8][9][10][11] In the present population-based study, we aimed to evaluate the impact of antibiotic exposure during the first 24 months of age on weight and height gain in healthy Finnish children carefully screened for other risk factors and chronic conditions potentially affecting linear growth.…”
mentioning
confidence: 99%
“…Indeed, antibiotics are known to promote growth in malnourished children. 29 The mechanisms of action are not known, although reduction in intestinal inflammation and resolution of EE may play an important role.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics were found to induce a growth-promoting effect in prepubertal children, possibly by altering their IM. 4 The neonatal IM composition is influenced by prenatal and postnatal antibiotic exposure 5 and other age-specific modifiers such as mode of delivery (natural birth vs cesarean delivery) and mother-to-infant transfer of bacterial strains and human milk oligosaccharides via breastfeeding. The latter are structurally diverse unconjugated glycans that are highly abundant in and unique to human milk; they can stimulate the growth and/or activity of healthy intestinal bacteria.…”
mentioning
confidence: 99%